Andalusia — the Golden Age’s shining example - Abd Razak, Dzulkifli (2005)
IT is fairly obvious that many of the practices of the culture of Andalusia are enshrined in the ideals and principles of Islam as emphasised in the Hadharic sense. In fact, the Golden Age of Islamic civilisation is a direct outcome of it, without having to attach any religious label to it. Physics, Abdus Salam, in his acceptance speech in Oslo, cited a specific case in Toledo as an example. As early as the 11th century, Toledo had been a centre for the transmission of knowledge, culture and science to Europe. Among the scholars who flocked to the place from all over Europe were Gerard of Cremona and John of Seville. Other famous translators were Peter Abelard of Bath, Robert of Chester, Stephenson of Saragossa, William of Lunis and Philip of Tripoli.